1987
DOI: 10.1097/00006123-198701000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Review of descending motor pathways involved with transcranial stimulation

Abstract: The anatomical basis of the pyramidal tract is reviewed with respect to its proposed role in the conduction of the motor evoked potential. The fiber diameter profiles are discussed in relation to the measured conduction velocities of the corticospinal tract in humans. Stimulus parameters utilized to obtain the motor evoked potential are reviewed in relation to the laterality of response, response threshold, and properties of spatial and temporal summation. A discussion of the major descending tracts involved w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
61
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(62 citation statements)
references
References 0 publications
1
61
0
Order By: Relevance
“…[1][2][3][4][5] The CST is known be involved mainly in movement execution of distal extremities, particularly fine-motor activities of the hand. [1][2][3][4][5] The CST originates from various cortical areas, such as the secondary motor area, the parietal cortex, and the primary motor cortex. The multiple cerebral origins of the CST appear to be important in terms of multiple functions of CST fibers and motor recovery mechanisms: perilesional reorganization following M1 injury.…”
mentioning
confidence: 99%
“…[1][2][3][4][5] The CST is known be involved mainly in movement execution of distal extremities, particularly fine-motor activities of the hand. [1][2][3][4][5] The CST originates from various cortical areas, such as the secondary motor area, the parietal cortex, and the primary motor cortex. The multiple cerebral origins of the CST appear to be important in terms of multiple functions of CST fibers and motor recovery mechanisms: perilesional reorganization following M1 injury.…”
mentioning
confidence: 99%
“…Previous animal studies [1][2][3]15] indicate that several possible motor pathways are responsible for the ability of these patients to walk, which include the crossing motor pathway from the lateral CST of the intact hemisphere. On the other hand, the ability in primates to take steps seems to require the sparing of at least one ventrolateral quadrant of the spinal cord, which allows the return of bilateral hindlimb locomotor activity [16].…”
Section: Discussionmentioning
confidence: 98%
“…It has been observed in the cat that bilateral sectioning of the ventrolateral quadrants of the cord prevents controlled evoked locomotion. Thus, the potential descending motor pathways that play a role in walking are the reticulospinal, vestibulospinal, and anterior CST pathways that lie in the ventrolateral quadrant of the cord [1]. Among these tracts, the role of the anterior CST pathway is not a feasible possibility, because it has been suggested that this tract in humans rarely descends below the upper thoracic portion of the spinal cord and that it primarily innervates the musculature of the neck, trunk, and proximal portions of the upper extremities [2].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations